The effect of high-performance fiber-reinforced cementitious composites on the lateral behavior of reinforced concrete frames without seismic details. (August 2020) - Saghafi, Mohammad Hossein; Golafshar, Ali; Zareian, Mohammad Sajjad; Kashani, Mohammad
Abstract: In areas with high seismicity, the construction of reinforced concrete structures with high ductility requires observance of the special seismic specifications of the ACI 318 regulations. This will increase the congestion of transverse reinforcement in the beam-column joints, and this reinforcement congestion in the joints in turn will bring along problems in the construction and concreting. In this study, the use of high-performance fiber-reinforced cementitious composites (HPFRCC) in the joints of frames has been investigated in order to prevent the congestion of the transverse reinforcement in beam-column joints. First, four half-scale exterior beam-column joints were tested under incremental cyclic lateral loading. The tested specimens consisted of two conventional concrete control specimens with and without seismic details and two HPFRCC specimens. Second, physical models for conventional concrete and HPFRCC joints were proposed. Third, verification was performed using experimental results. Then, 5 and 10-story frames including two conventional control frames with and without seismic details and two HPFRCC frames without seismic details are developed by assembling these physical models with OpenSees software. Using nonlinear analyses, the ductility ratio, energy dissipation capacity as well as the cyclic behavior of the frames are examined and compared. The results show that the use of HPFRCC in beam-column joints of frames without seismic details increases the shear strength of joints, the relocation of plastic hinge to the outside of the joint core and the improvement of lateral behavior. The proposed method also shows a significant improvement in seismic parameters such as strength, stiffness, energy dissipation and ductility capacity.